Preventive solutions needed on dangerous dogs (Veterinary record, 2012)
CONCERN that government plans for tackling irresponsible dog ownership do not offer any preventive solutions to the problem has been expressed by the BVA, the British Small Animal Veterinary Association (BSAVA) and the Society of Practising Veterinary Surgeons (SPVS) in their joint response to a recent Defra consultation on the subject.